2D ELECTRICAL RESISTIVITY TOMOGRAPHY FOR THE ASSESSMENT OF MINERALS’ OCCURRENCES IN UGONEKI, EDO STATE, SOUTH-SOUTH, NIGERIA - Onifade, Y. S.; Olaseni, V. B.; Baoku, I. G.; Eravwodoke, C. (FUDMA JOURNAL OF SCIENCES, 2021)
Geophysical investigation using the 2D Electrical Resistivity Tomography (ERT) was carried out to assess the subsurface of Ugoneki and its environs in order to investigate for minerals. A total of six (6) traverses, 200 m long each, three (3) transverse lines were in the North-South direction and the other three (3) traverses in the West-East direction using the Wenner electrode configuration. 2D Wenner resistivity data were acquired along each traverse. The data were inverted to reveal a spatially continuous resistivity distribution in 2D within the study area. The 2D results reveal a depth of 39.6 m across each traverse. Resistivity values vary from 87.1 – 3423 Ωm in the entire study area. From the standard resistivity table, the following solid and non-metallic type of minerals can be delineated in the study area which is representative of sandy clay, lateritic clay sand, sandstone and limestone with resistivity values that range from 87.1 – 89.9 Ωm, 1201 – 1462 Ωm, 2069 – 3423 Ωm, and 2069 – 3423 Ωm respectively. The implication of this research is to know the type and the particular location where these non-metallic solid minerals are located in the subsurface for future exploration. The results of resistivity values are compared with those in the literature and are found to be in good agreement. In order to quantify these minerals, it is also recommended to use higher dimension (3D) of resistivity method (ERT) in the study area.